2006
DOI: 10.1111/j.1750-3841.2006.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Reduced‐Fat Frankfurter Modified by Konjac–Starch Mixed Gels

Abstract: Konjac–potato starch mixed gels were incorporated into reduced‐fat (18%) frankfurters and compared with reduced‐fat (18% fat, C18) and high‐fat (28% fat, C28) controls for textural, sensory properties, and storage stability. At the same konjac concentration, increasing starch level resulted in lower G′ (storage modulus) and G″ (loss modulus) of the konjac–potato starch mixtures leading to more elastic‐mixed gels. No differences in textural hardness among gel‐added treatments were noticed. C28 had the lowest se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…As compared with the normal-fat control (C), partial replacement of the pork backfat by konjac gel (F/KG) did not affect (P> 0.05) lightness (L*) and produced a slight but significant decrease of a* and b*. Jiménez-Colmenero et al (2010a), Kao and Lin (2006) and Lin and Huang (2003) found that the effect of the addition of konjac gel on the color of the frankfurters was affected by the proportion of this fat replacer, so that in formulations containing 19% konjac gel to reduce fat, L* and b* values decreased and a* values increased compared with full-fat frankfurters. No differences in the color parameters were observed between full-fat products and reduced-fat products containing konjac (2%)-potato starch (4%) mixed gels (Kao & Lin, 2006).…”
Section: Colormentioning
confidence: 97%
See 1 more Smart Citation
“…As compared with the normal-fat control (C), partial replacement of the pork backfat by konjac gel (F/KG) did not affect (P> 0.05) lightness (L*) and produced a slight but significant decrease of a* and b*. Jiménez-Colmenero et al (2010a), Kao and Lin (2006) and Lin and Huang (2003) found that the effect of the addition of konjac gel on the color of the frankfurters was affected by the proportion of this fat replacer, so that in formulations containing 19% konjac gel to reduce fat, L* and b* values decreased and a* values increased compared with full-fat frankfurters. No differences in the color parameters were observed between full-fat products and reduced-fat products containing konjac (2%)-potato starch (4%) mixed gels (Kao & Lin, 2006).…”
Section: Colormentioning
confidence: 97%
“…One such ingredient is konjac (glucomannan)-based fat analogue. Konjac gels have been used to simulate fat characteristics and reduce the fat content in different meat products, including frankfurters (Jiménez-Colmenero et al, 2012;Kao & Lin, 2006;Lin & Huang, 2003;Osburn & Keeton, 2004). As a strategy to improve fatty acid profiles (decrease SFA, and increase MUFA and PUFA levels) of frankfurters, various vegetable oils (olive, cottonseed, corn, soya bean, peanut, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The list of ingredients investigated as meat extenders and or substitutes includes cereal grains (Beggs, Bowers, & Brown, 1997;Skrede, 1989), dairy sources (Atughonu, Zayas, Herald, & Harbers, 1998), fruits and vegetables (Aleson-Carbonell, Fernandez-Lopez, Sayas-Barbera, & Perez-Alvarez, 2003;Revilla & Quintana, 2005), legumes (Dzudie, Scher, & Hardy, 2002;Hinds, 2001;Lin, Huff, & Hsieh, 2000;Lin & Mei, 2000;Muguerza, Ansorena, & Astiasaran, 2003;Rossi, 1988), roots and tubers (Annor-Frempong, Annang-Prah, & Wiredu, 1996;Kao & Lin, 2006), and single-cell sources (Bruna, Fernandez, Hierro, De La Hoz, & Ordonez, 1999;Bruna et al, 2003;Lin & Lin, 2004). Annor-Frempong et al (1996) used cassava flour as a substitute to fat in comminuted pork sausages and reported that 9% of cassava flour could be used in place of fat without any compromise on organoleptic quality.…”
Section: Introductionmentioning
confidence: 99%
“…The lightness of KG increased (P < 0.05) and redness was not affected (P > 0.05) by storage time, but no clear relation with yellowness was observed (Table 1). This effect appears to have only limited effects on product formulation since it has generally been reported that addition of KG to reduced-fat frankfurters has little influence on colour perception (Kao & Lin, 2006;Lin & Huang, 2003). Different behaviour of L* as affected by chilling storage has been reported in konjac gel used for restructured seafood products .…”
Section: Effect Of Chilling Storagementioning
confidence: 99%
“…Moreover, because of its technological properties, when combined with other ingredients (starch, carrageenates, gellan gum) konjac can be used as a 'fat analogue' in the formulation of reduced/low-fat meat products. Konjac (added in different ways and concentrations) has been used to reduce fat in products such as frankfurters (Jiménez-Colmenero et al, 2010;Kao & Lin, 2006;Lin & Huang, 2003;Osburn & Keeton, 2004), bologna (Chin, Keeton, Longnecker, & Lamkey, 1998a, 1998bChin, Keeton, Miller, Longnecker, & Lamkey, 2000), fresh sausages (Osburn & Keeton, 1994) and pork nuggets (Berry & Bigner, 1996).…”
Section: Introductionmentioning
confidence: 99%